Regulating the Rating Agencies - Claire A. Hill (Washington University Law Quarterly, 2004)
The major rating agencies—Moody’s Investor Services, Standard and Poor’s, and Fitch—rate debt instruments and companies. A debt instrument’s rating principally reflects whether the instrument is likely to be repaid on a timely basis, and, increasingly, the amount that might be recovered should the instrument default. The rating agencies’ terminology, and in particular, the designation for the highest rating category, AAA, has entered into everyday parlance; high quality items of all sorts are not infrequently referred to as AAA rated. This Article proceeds as follows. Part II provides background information about rating agencies and gives a brief history and description of the rating agency regulatory regime and the changes being considered. The part also considers the extent to which the rating agencies compete against each other. Part III appraises rating agency performance. How good a job do rating agencies do? Does issuer willingness to pay for ratings, and market willingness to accept lower interest rates on rated securities, reflect value that rating agencies provide? If so, what is the source of that value? Do ratings merely provide favorable regulatory treatment, or do they also provide information? Part III discusses answers to these questions. Part IV discusses the case for reform of the regulatory regime applicable to rating agencies and appraises reform proposals. Part V concludes.
Keywords: Rating agencies (Finance); Securities – International regulation; Corporate reform